TEACHING STORY-MAKING AS AN IMPORTANT TOOL FOR DEVELOPING CONNECTED SPEECH OF PRESCHOOL CHILDREN (Scientific journal of the Fergana State University, 2024)
This article talks about the fact that one of the main tasks of raising and teaching preschool children is the development of speech and oral communication, and it is possible to develop connected speech by teaching them to compose a story.